Qualitative Study of Entrepreneurial Marketing and Performance of Village-Owned Enterprises (VOEs) In Indonesia - Makmur Makmur; Norhidayah Mohamad; Siti Norbaya (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Objective: The performance of village-owned enterprises is examined in this study along with the key components of the entrepreneurial marketing idea. The degree to which current marketing techniques align with entrepreneurial marketing strategies is also evaluated. Research Design & Methods: This study uses a qualitative research design and semi-structured in-depth interviews with 12 directors of chosen village-owned enterprises. The interviews were based on seven components of the entrepreneurial marketing concept: financial performance and non-financial performance. The ATLAS.ti program was used to facilitate the thematic analysis of the gathered data. Findings: The research conclusions demonstrate that village-owned enterprises have been successful in incorporating entrepreneurial marketing ideas, which are crucial to their operations. Contribution & Value Added: The main contribution behind this study is the lack of empirical research on entrepreneurial marketing from the perspective of village-owned enterprises.